COPPER MINERALS FROM THE OXIDATION ZONE OF THE SARYSHAGAN Cu(Mo)-PORPHYRY DEPOSIT (WESTERN BALKHASH REGION, CENTRAL KAZAKHSTAN) - S.V. Pribavkin; А.V. Korovko; G.Yu. Shardakova; А.V. Аntonishin (Минералогия)
The paper describes secondary Cu minerals from the oxidation zone of the Saryshagan Cu (Mo)- porphyry occurrence (Western Balkhash region, Central Kazakhstan). The zonal distribution of secondary Cu minerals is shown along the section of the oxidation zone. Malachite and chrysocolla are found in the lower part of the section, whereas chrysocolla and Cu chlorides are dominant in the upper zone. Cu chlorides include atacamite, spangolite and unidentified minerals and are associated with gypsum. The local presence of fissure-hydrogenic U mineralization is established.